The Effect of Online Visibility on Purchase Intention Through Company Reputation as a Mediating Variable (Case Study: Villa Kintamani) - Jero Wahyu ABDI; Ni Made WAHYUNI; Ni wayan SITIARI (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the effect of online visibility on tourists' purchase intention, with corporate reputation as a mediating variable, in the context of three villas located in the Kintamani area of Bali. The research employed a quantitative approach with an associative method. The population consisted of tourists who had previously stayed at or visited the three villas. A total of 90 respondents were selected using a non-probability sampling technique with a purposive sampling approach. Data were collected through the distribution of questionnaires as the primary research instrument. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results indicate that online visibility has a positive and significant effect on tourists’ purchase intention, as well as on corporate reputation. Furthermore, corporate reputation also has a positive and significant effect on tourists’ purchase intention. Another important finding reveals that corporate reputation significantly mediates the relationship between online visibility and purchase intention. Overall, the findings suggest that online visibility plays a strategic role in shaping tourists’ purchase intentions, both directly and indirectly through enhanced corporate reputation. Therefore, it is recommended that integrated digital marketing strategies be implemented, with simultaneous attention to both online visibility and corporate reputation, in order to increase consumer interest and purchasing decisions in the context of rural tourism.